Systematics Literature Review: The use of learning media to improve student's mathematical creative thinking skills in 21st century learning - Qoriaturrosyidah, Fitri; Simanjuntak, Friska Yanti; Mawaddah, Dina; Daniel Marpaung, Carlos Bettran; Hanggara, Yudhi; Ismarti, Ismarti; Hartanto, Suryo; Hermansah, Hermansah (CAHAYA PENDIDIKAN, 2025)
This research aims to review the literature related to the use of learning media in enhancing mathematical creative thinking skills. The method applied in this research is the Systematic Literature Review (SLR). As many as 20 articles were used as data sources in this study. Data were collected by reviewing all articles obtained from the period 2018 to 2023. To complete this research, various journal articles were collected through Google Scholar with the help of the Harzing's Publish or Perish application. The keywords in this article are "learning media and mathematical creative thinking skills." The research results show that the R&D (Research and Development) research method is used more frequently, accounting for 55%, compared to other research methods, with the topic of using electronic learning media to enhance students' mathematical creative thinking skills. Furthermore, the use of electronic learning media, such as e-comics, e-modules, learning videos, educational games, mobile learning, edutainment games, visual videos, Adobe Flash Professional, Go-Metra board games on geometry transformation material, Articulate Storyline 3, and e-learning, is effective in improving students' mathematical creative thinking skills. It is hoped that the results of this research can provide useful information for other researchers and assist educators in applying learning media to enhance students' mathematical creative thinking skills in the 21st-century learning era.